Tribotechnical properties of high chromium alloys are in the cast stay and after heat treatment - Киндрачук, М.В.; Куцова, В.З.; Ковзель, М.А.; Гребенева, А.В.; Данилов, А.П.; Хлевна, Ю.Л. (Problems of Tribology, 2014)
A structure, phase composition, tribotechnical characteristics, hardness, microhardness of structural components of 28Х32Н3Ф high-chromium cast-iron of and nickel-chromium alloy «Nikorim», are studied at present worse. It was shown that after heat treatment has the best structure have sample of cast-iron, heat treatment regime: Тaust. = 1050 °С, τisoth. = 1 h., Тaust. = 350 °С, τisoth. = 3 h. The maximum hardness and wear resistance have sample after treatment on this regime.